The Inhibitory Effects of Trastuzumab on Corneal Neovascularization - Guler, Mete; Yilmaz, Turgut; Ozercan, Ibrahim; Elkiran, Tamer (Elsevier Science Inc, 2009)
PURPOSE: To investigate the effect of systemic administration of trastuzumab in the prevention of experimentally induced corneal neovascularization in a rat model. DESIGN: An experimental animal study. METHODS: Sixteen male Wistar,Albino rats weighing 250 g to 300 g were used in the study. Silver nitrate sticks (75% silver nitrate, 25%) potassium nitrate) were used to induce chemical cauterization on the corneas of 16 eyes. The rats were randomized to 1 of 2 groups: Group 1 (n = 8) received intraperitoneally 1 ml (4 mg/kg) trastuzumab and Group 2 (n = 8) received 1 ml saline. The corneal surface covered with neovascular vessels was measured on the photographs as the percent, age of the total area of the cornea by using computer imaging analysis on the eighth day. The corneas obtained from rats were evaluated for vascular endothelial growth factor (VEGF) immunostaining semicantitatively. The number of the corneal neovascularizations were also determined on slides. The results were evaluated with the Mann-Whitney U test. RESULTS: The burn stimulus was similar between groups. The average neovascularization area in treatment group was statistically smaller than control (P = .008). The mean VEGF staining intensity of epithelial and endothelial layers of cornea in treatment group was less than control (P = .038 and P = .041, respectively). The stroma of the treatment group showed less staining, but the difference was not significant (P = .056), The number of corneal neovascularizations on slides in trastuzumab treated eyes were less than the control group (P = .02). CONCLUSION: Systemic administration of trastuzumab is effective in prevention of the corneal neovascularization. (Am J Ophthalmol 2009;147:703-708. (C) 2009 by Elsevier Inc. All rights reserved.)
Keywords: Endothelial Growth-Factor; Breast-Cancer; in-Vitro; Bevacizumab Avastin; Angiogenesis; Herceptin; Mechanisms; Expression; Vivo; Resistance